The regional engagement of universities under a stakeholders’ analysis approach: An empirical framework - Adamakou, Maria; Niavis, Spyros; Kallioras , Dimitris; Petrakos, George (Το Βήμα των Κοινωνικών Επιστημών, 2022)
In the knowledge era, universities have been gaining a vital role in fostering regional development. The active role of universities in promoting regional targets can be seen as the “third mission” of universities. Towards acting as regional development carriers, universities need to establish networks and partnerships with other regional actors, both public and private, that are working in the same direction. The paper adopts a stakeholders’ analysis approach to develop and test an empirical framework for evaluating the regional engagement of universities. Particularly, the paper provides clear-cut empirical responses to a couple of research questions: a) How do regional stakeholders perceive the regional engagement of universities? b) What is the level of perceptions alignment at each particular dimension of regional engagement? The University of Thessaly, in the homonymous Region, is selected as the case-study. Particular dimensions of regional engagement are highlighted and for each dimension relevant items are selected to quantify the perceptions of stakeholders. The stakeholders’ responses are incorporated into statistical analyses to extract the score for each dimension item and to test for any existing different among different types of stakeholders (namely, representatives from the university, the civil society, and the business sector).